Associations between music training and the dynamics of writing music by hand. (March 2023) - Bertiaux, Aurélien; Gabrielli, François; Giraud, Mathieu; Levé, Florence
Learning to write music in the staff notation used in Western classical music is part of a musician's training. However, writing music by hand is rarely taught formally, and many musicians are not aware of the characteristics of their musical handwriting. As with any symbolic expression, musical handwriting is related to the underlying cognition of the musical structures being depicted. Trained musicians read, think, and play music with high-level structures in mind. It seems natural that they would also write music by hand with these structures in mind. Moreover, improving our understanding of handwriting may help to improve both optical music recognition and music notation and composition interfaces. We investigated associations between music training and experience, and the way people write music by hand. We made video recordings of participants' hands while they were copying or freely writing music, and analysed the sequence in which they wrote the elements contained in the musical score. The results confirmed experienced musicians wrote faster than beginners, were more likely to write chords from bottom to top, and they tended to write the note heads first, in a flowing fashion, and only afterwards use stems and beams to emphasize grouping, and add expressive markings.